Evaluating the effectiveness of field-based probiotic treatments for stony coral tissue loss disease in southeast Florida, USA - Kelly A. Pitts; Mackenzie Scheuermann; Jonathan S. Lefcheck; Blake Ushijima; Natalie Danek; E. Murphy McDonald; Aaron R. Milanese; Monica D. Schul; Julie L. Meyer; Kathryn A. Toth; Zachary Ferris; Yesmarie T. De La Flor; et al. (Frontiers in Marine Science, 2025)
Stony coral tissue loss disease (SCTLD) has spread throughout Florida’s Coral Reef, causing extensive mortality of over 30 species of reef-building corals, and has rapidly spread to many other countries and territories throughout the Caribbean. Current treatments for SCTLD, including a proprietary paste mixed with the antibiotic amoxicillin, do not provide protection from future infections and may select for antibiotic-resistant pathogenic bacteria. In contrast, beneficial microorganisms (i.e., probiotics), may directly treat or act as prophylactics for corals exposed to SCTLD. This study investigated the use of the bacterium Pseudoalteromonas sp. McH1-7, previously isolated from a SCTLD-resistant fragment of Montastraea cavernosa , as a potential probiotic treatment for SCTLD-infected M. cavernosa colonies in the wild. We developed and tested two probiotic deployment methods: (1) the injection of a probiotic in seawater suspension into a weighted bag placed over the coral to treat the whole colony; and (2) a sodium alginate-based paste that was applied directly to each disease lesion. After treatment, the disease progression of each colony was routinely monitored using three-dimensional photogrammetry for 2.5 years. Slurries of tissue and mucus samples were taken from healthy and diseased colonies before treatment, two weeks after treatment, and three months after treatment to identify possible shifts in bacterial and archaeal communities. McH1–7 successfully slowed SCTLD lesion progression for 2.5 years following treatments when delivered using the whole-colony treatment technique. Our assessment of the microbiome following treatment showed that McH1–7 was effective without dominating bacterial communities among infected corals. In contrast, corals treated with the probiotic paste lost more tissue than corals treated with the control paste, indicating that the lesion-specific probiotic paste is not effective at stopping SCTLD. Probiotic inoculations via a whole-colony treatment technique may provide a path toward slowing the loss of reef-building corals due to SCTLD.